Growth and neurodevelopmental outcome in newborns with congenital non-cardiac surgical anomalies: A single-centre retrospective study - Amit Trivedi; Kathryn Browning Carmo; Kristen James-Nunez; Adrienne Gordon (Elsevier, 2023)
Background: Survival of infants with congenital anomalies has increased dramatically, shifting the focus of clinical care and research toward optimising growth and neurodevelopment. Objective: To evaluate growth and determine the impact of growth on neurodevelopmental outcomes of neonates born at term gestation with congenital non-cardiac surgical anomalies (NCSA), who required a laparotomy. Methods: This was a single-centre retrospective cohort study. Demographic details, measurements of growth, and mean scores of Bayley Scales of Infant and Toddler Assessment, third edition, were collected. Means z-scores of growth measurements at birth, discharge and one-year-assessment were compared. Regression analysis was performed to explore predictive ability of growth measurements on mean scores of developmental assessment. Results: A total of 105 infants were included. Mean z-scores for weight (-0.85) and head circumference (-0.34) at birth, though below population mean, were age-appropriate. Statistically significant decrease in z-score for weight was noted at discharge. Mean scores across the domains developmental assessment were normal. Z-scores for weight and height at one-year assessment predicted scores of gross motor (p-value 0.005) and cognitive development (p value 0.03) respectively. Conclusions: Neonates born at term gestation with NCSA had normal growth at birth. Postnatal growth restriction was noted at discharge. This loss in growth was not fully recouped at one-year assessment. As growth failure at one-year assessment could predict scores of developmental assessment, this group of infants needs careful nutritional and developmental monitoring.